Financial technology and renewable energy transition in Africa - Justice Gyimah; Joshua Kojo Bonzo (Results in Engineering)
Addressing climate change issues, coupled with achieving the Sustainable Development Goals, continues to be a global battle, despite the efforts made. Since the impact of climate change significantly affects vulnerable regions such as Africa, achieving sustainable environment is paramount for the region. Therefore, this current study investigates the effects of financial technology (fintech), globalization, economic growth, and industry value added on renewable energy consumption in West Africa from 2000 to 2022 using the fixed and random effects, as well as the Augmented Mean Group (AMG) methods. The findings are as follows: first, fintech’s impact on renewable energy consumption is negative and significant. Thus, at a 1 % significance level, fintech reduces renewable energy consumption by 0.0161. Second, the effect of economic growth on renewable energy consumption is insignificant, with a negative coefficient of 0.0044. Third, globalization has an insignificant effect on renewable energy consumption, with a negative coefficient of 0.0098. Fourth, industry value added with a positive coefficient of 0.0067 is not significant in affecting renewable energy consumption in the region. These findings encourage the incorporation of clean technologies in production.